Analysis Of The Implementation Of Productive Finance In Sharia Commercial Bank (Bus) In Padang City - Anggraini, Misi; Wira, Ahmad; Duhriah, Duhriah (WADIAH, 2025)
Mudharabah and musyarakah contracts as productive financing do not yet dominate in sharia financial institutions. However, in practice there are problems, one of which is related to the implementation of the contract. The aim of the research is to determine the implementation of Mudharabah and musyarakah contracts in Productive Financing carried out by Sharia Commercial Banks (BUS) along with the feasibility of approval for productive financing at Sharia Commercial Banks (BUS) in Padang City what's in it. The research method uses qualitative methods. The case study approach was carried out through interviews with Sharia Commercial Banks (BUS) which implement productive financing. The natural observation approach was carried out through the appointment of four volunteers who had been appointed and determined by researchers to identify the application of financing for MSMEs in Padang. The results show that the implementation of productive financing at Sharia Commercial Banks (BUS) in Padang City shows two Sharia Commercial Banks implementing mudharabah and musyarakah contract financing for MSMEs. The implementation of mudharabah and musyarakah contracts carried out by Sharia Commercial Banks (BUS) in Padang City is in line with theory, the MUI DSN Fatwa and previous research for the implementation of Sharia Commercial Banks in Padang City.